Pengaruh Pengeluaran Pemerintah, Investasi Swasta dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Bali - Arvi Veteriyanthi, Gusti Ayu Putu; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Economic development is one of the main goals for countries that are developing. Economic development will facilitate economic growth that has been planned for each year in the economic performance of a country or region. At the macro-economic scale of economic growth measured by Gross Domestic Product (GDP). The implications of this development is expected to be increased employment opportunities, income level increases, and the prosperity of society is becoming increasingly high, so we need more greater infrastructure by the government, the higher the level of education and the use of technology is increasing. The purpose of this study was to determine the effect of government spending, private investment, labor to economic growth districts / cities in the province of Bali. This study uses panel data for five years in nine districts / cities in Bali resulting in a forty-five observations. The technique used in this study linear analysis. Research results obtained are in government spending, private investment and employment simultaneously affect the economic growth and partially positive and significant impact on economic growth the district / city in the province of Bali. The most dominant variable affecting economic growth districts / municipalities in the province of Bali is the Government Expenditures.
Keywords: Economic Growth, Government Spending, Private Investment, Labor